2001
DOI: 10.2176/nmc.41.177
|View full text |Cite
|
Sign up to set email alerts
|

Vasodilatory Effect of Basic Fibroblast Growth Factor in Isolated Rat Cerebral Arterioles: Mechanisms Involving Nitric Oxide and Membrane Hyperpolarization.

Abstract: Basic fibroblast growth factor (bFGF), a potent mitogen, acutely dilates cerebral blood vessels and may be effective in reducing cerebral infarction. However, the vasodilatory mechanism, which may involve nitric oxide (NO), is not completely understood. This study investigated whether membrane hyperpolarization is also involved in this mechanism. Membrane potential (MP) of smooth muscle cells and vessel diameter of isolated intracerebral arterioles were simultaneously measured following extraluminal applicatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2010
2010
2014
2014

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…99 It has also been reported that K ATP channel activation mediates parenchymal arteriolar membrane hyperpolarization in response to basic fibroblast growth factor. 100 Glibenclamide-sensitive K ATP currents measured in pial artery SMCs are activated by synthetic vasodilators such as pinacidil, as well as by endogenous vasodilators such as calcitonin gene-related peptide and VIP. 101,102 While there is evidence that supports the presence of K ATP channels in parenchymal arteriolar SMCs, the biophysical properties of K ATP channels in these vessels are not known, and the functional role of K ATP channels in regulating parenchymal arteriolar tone requires further characterization.…”
Section: K+ Channels In the Control Of Parenchymal Arteriolar Tonementioning
confidence: 99%
“…99 It has also been reported that K ATP channel activation mediates parenchymal arteriolar membrane hyperpolarization in response to basic fibroblast growth factor. 100 Glibenclamide-sensitive K ATP currents measured in pial artery SMCs are activated by synthetic vasodilators such as pinacidil, as well as by endogenous vasodilators such as calcitonin gene-related peptide and VIP. 101,102 While there is evidence that supports the presence of K ATP channels in parenchymal arteriolar SMCs, the biophysical properties of K ATP channels in these vessels are not known, and the functional role of K ATP channels in regulating parenchymal arteriolar tone requires further characterization.…”
Section: K+ Channels In the Control Of Parenchymal Arteriolar Tonementioning
confidence: 99%
“…Vascular studies have demonstrated that the vasoactive action of FGF2 is mediated in part by K ATP channels (Cuevas et al 1991;Boussairi and Sassard 1994;Tiefenbacher and Chilian 1997;Kajita et al 2001). Both cardiac sarcK ATP and mitoK ATP channels have been implicated in I-R injury and to be important effectors of cardioprotection, including ischemic preconditioning (Schultz et al 1997;Gross and Fryer 1999;Grover and Garlid 2000;O'Rourke 2000).…”
Section: Sarcolemmal and Mitochondrial K Atp Channel Involvement In F...mentioning
confidence: 99%
“…Certain biological actions, in particular vascular and angiogenic functions, of FGFs have been shown to occur through nitric oxide (NO) signaling (Huang et al 1997;Tiefenbacher and Chilian 1997;Cuevas et al 1999;Hampton et al 2000;Parenti et al 2001) or ATPsensitive potassium (K ATP ) channel activity (Cuevas et al 1991;Boussairi and Sassard 1994;Tiefenbacher and Chilian 1997;Kajita et al 2001). Hampton and colleagues determined that exogenously FGF2 applied prior to ischemia was able to protect the heart from postischemic dysfunction in hearts in an inducible nitric oxide synthase (iNOS)-dependent manner (Hampton et al 2000).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation